INFLATION, THE RUPIAH EXCHANGE RATE AND THEIR IMPACT ON THE ISLAMIC SOCIAL REPORTING OF CONSUMER GOODS INDUSTRY COMPANIES LISTED IN THE INDONESIAN SHARIA STOCK INDEX (ISSI) FROM 2014-2018 - Andini Nurwulandari (International Journal of Islamic Khazanah, 2019)
Apart from serving as a forum for parties in need of funds (issuers) and those with excess funds, investment in the capital market is one of the investments currently being developed in society (investors). The Islamic capital market is a capital market that is governed by sharia principles; all securities transactions on the capital market are governed by sharia provisions. This is a quantitative study that makes use of time series data, which consists of a single object but spans multiple periods: Inflation, Rupiah Exchange Rates, and Stock Prices from 2014 to 2018. The method used is a causal and distributive historical method. The population for this study is the entirety of the Indonesian Sharia Stock Index in the Consumer Goods Industry Sector, which consists of 29 companies listed on the ISSI. The Multicollinearity Test, the Autorelation Test, the Linearity Test, and the Fixed Effect Model were used to analyze the data. This study shows that: 1) The inflation variable has a significant and significant impact on stock prices in the Indonesian Sharia Stock Index (ISSI), on the basis of results from the partial test of the first hypothesis: 2) The results of the second hypothesis partial test indicate a substantial effect on the Indonesian Sharia stock index share price of the variable Rupiah Exchange rate (ISSI).